Analisis Penerapan Konsep Syariah Pada Hotel Sago Bungsu (Tinjauan Fatwa DSN MUI NO: 108/DSN-MUI/X/2016) - Zilal Afwa Ajidin (Jurnal Manajemen, 2019)
ABSTRACT Nowadays sharia hotels are one of the business sectors in the halal industry that is growing rapidly, especially in Lima Puluh Kota Regency, West Sumatra. This study aims to determine the implementation of the sharia concept in the Sago Bungsu hotel according to the Fatwa of the National Sharia Council (DSN) of the Indonesian Ulema Council (MUI) No. 108 / DSN-MUI / X / 2016 concerning sharia hotels. This research is a qualitative research with a descriptive explorative approach. The method used is in-depth interviews to Sago Bungsu Hotel Managers and hotel consumers with observation and documentation models. The results of this study indicate that the implementation of sharia concept in the Sago Bungsu hotel in Lima Puluh Kota District is in accordance with the MUI DSN fatwa No: 108 / DSN-MUI / X / 2016. Keywords: Sharia Concept, Sago Bungsu Hotel, Fatwa DSN MUI